2021
DOI: 10.1186/s12906-021-03210-8
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology modeling identifies synergistic interaction of therapeutic and toxicological mechanisms for Tripterygium hypoglaucum Hutch

Abstract: Background Tripterygium hypoglaucum Hutch (THH) both has prominent efficacy and unwarranted toxicity in the treatment of autoimmune diseases. Nevertheless, its pharmacological and toxicological profiles still remain to be elucidated. In the current study, the network pharmacology approach was applied to identify synergistic interaction and mechanism of efficacy and toxicity for THH from a holistic perspective. Methods The compounds from THH were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…28 Two different network pharmacology studies suggest that the PI3K/AKT pathway is linked to the effectiveness of hydroxychloroquine and tripterygium hypoglaucum as treatments for SLE. 29,30 Furthermore, Jie Wang et al demonstrated that azithromycin could enhance the alternatively activated macrophage phenotype to alleviate SLE via the PI3K/AKT pathway. 31 In SLE, the PI3K/ AKT pathway also contributes to the progression of organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…28 Two different network pharmacology studies suggest that the PI3K/AKT pathway is linked to the effectiveness of hydroxychloroquine and tripterygium hypoglaucum as treatments for SLE. 29,30 Furthermore, Jie Wang et al demonstrated that azithromycin could enhance the alternatively activated macrophage phenotype to alleviate SLE via the PI3K/AKT pathway. 31 In SLE, the PI3K/ AKT pathway also contributes to the progression of organ damage.…”
Section: Discussionmentioning
confidence: 99%